(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The problem is that the student is aware of new knowledge, new methods, new advanced technology and behavioral problems. If the student does not get the starting point for his creative search to overcome the difficulty, he cannot think about it. So the student does not accept it to solve it.